2011
DOI: 10.1161/circresaha.110.235028
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor 3 Promotes Recruitment of Monocyte/Macrophages in Inflammation and Atherosclerosis

Abstract: Rationale:The role of sphingosine-1-phosphate (S1P) and its receptors in the pathogenesis of atherosclerosis has not been investigated. Objective:We hypothesized that the S1P receptor 3 (S1P 3 ) plays a causal role in the pathogenesis of atherosclerosis. Methods and Results:We examined atherosclerotic lesion development in mice deficient for S1P 3 and apolipoprotein (Apo)E. Although S1P 3 deficiency did not affect lesion size after 25 or 45 weeks of normal chow diet, it resulted in a dramatic reduction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
167
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 38 publications
(54 reference statements)
7
167
1
1
Order By: Relevance
“…Strikingly, at flow rates similar to physiological (2-5 dynes/cm 2 ), mononuclear cell adhesion to endothelial cells pretreated with LPS plus S1P showed a similar resistance to shear stress than cells pretreated with TNF-a, although the number of cells attached was not as high as with TNF-a, which argues for a minimal threshold of adhesion molecules required for a strong cell adhesion. These observations are consistent with earlier reports showing that exposure to S1P increases surface expression of adhesion molecules in endothelial cells (9,28) and that the S1P-S1P 3 axis promotes leukocyte recruitment in inflammation and atherosclerosis (29). However, our results differ from studies in which S1P prevents TNF-a-mediated monocyte adhesion to aortic endothelium in mice (30), and S1P protects ischemiareperfusion via S1P 3 by suppressing leukocyte adhesion (31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Strikingly, at flow rates similar to physiological (2-5 dynes/cm 2 ), mononuclear cell adhesion to endothelial cells pretreated with LPS plus S1P showed a similar resistance to shear stress than cells pretreated with TNF-a, although the number of cells attached was not as high as with TNF-a, which argues for a minimal threshold of adhesion molecules required for a strong cell adhesion. These observations are consistent with earlier reports showing that exposure to S1P increases surface expression of adhesion molecules in endothelial cells (9,28) and that the S1P-S1P 3 axis promotes leukocyte recruitment in inflammation and atherosclerosis (29). However, our results differ from studies in which S1P prevents TNF-a-mediated monocyte adhesion to aortic endothelium in mice (30), and S1P protects ischemiareperfusion via S1P 3 by suppressing leukocyte adhesion (31).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, S1P 3 has been pinpointed as the receptor involved in proadhesive S1P effects, while S1P 1 would account for its anti-adhesive properties in in vitro studies, suggesting S1P receptor subtype specificity (36). Furthermore, the role of S1P 3 in atherogenesis has recently been emphasized by a report demonstrating that S1P 3 promotes recruitment of monocytes/macrophages in inflammation and atherosclerosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…4). Keul et al showed that the recruitment of monocytes that contributed to atherosclerosis was dependent on S1P 3 (30). Because S1P 3 acts as a modulator of SDF-1-mediated chemotaxis, differential expression is likely responsible for the differences in SDF-1α-mediated chemotaxis between the two subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…45 An S1P 1 -selective agonist may act directly on macrophage proliferation and trafficking. [26][27][28][29]46 An in vivo proliferation assay demonstrated that CYM did not affect macrophage proliferation. Increasing amounts of data have indicated that the lower number of macrophages in the inflamed tissues of FTY720-treated mice could be an indirect effect of vascular permeability and monocyte recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…S1P might also be involved in macrophage trafficking. 3,[26][27][28][29] FTY720 reduces macrophage infiltration into sites of inflammation in many inflammatory disease models. [30][31][32][33] The mechanism of action of FTY720 may involve its effects on endothelial cells to reduce monocyte migration.…”
Section: Introductionmentioning
confidence: 99%